Additively manufactured anatomical heart model for performance evaluation of aortic valve implants (Transactions on Additive Manufacturing Meets Medicine, 2020)
It is suspected that the minimal invasive implantation of aortic valves (TAVI procedure) causes damage to the implant that affects its performance. Medical simulators can be used to investigate this suspicion systematically, repeatedly and under constant conditions. This paper describes the development of a heart model that extends the existing HANNES simulator for aortic valve performance evaluation. The advantages of additive manufacturing (AM) are used to provide an anatomically realistic replication of the relevant anatomical sections of the heart and the aortic root.
Keywords: minimal invasive implantation; aortic valve